Mild Behavioral Impairment: An Early Sign and Predictor of Alzheimer's Disease Dementia - Jiang, Fei; Cheng, Cheng; Huang, Jinsong; Chen, Qiaoling; Le, Weidong (Current Alzheimer Research, 2022)
Background: Alzheimer's disease (AD) is the most common form of dementia in the elderly population and places heavy burdens on medical care and nursing. Recently, the psychiatric and behavioral symptoms of prodromal AD, especially mild behavioral impairment (MBI), have attracted much attention. In 2012, Alzheimer's Association International Conference, MBI was proposed as a syndrome with psychiatric and behavioral disturbance before the onset of typical clinical cognitive symptoms in dementia. Increasing lines of evidence have indicated the link between MBI and early AD pathologies including Aβ and tau. Objective: This narrative review aims to summarize the advantages of MBI over other concept of psychiatric and behavioral symptoms associated with AD in the early prediction of AD dementia. We also discuss the possible common genetic basis and pathological mechanisms underlying the interactions between MBI and AD. Methods: Papers cited here were retrieved from PubMed up to February 2022. We selected a total of 95 articles for summary and discussion. Results: The occurrence of MBI is mainly due to the overlapped genetic and pathological risk factors with AD and is related to the brain's response to environmental stressors. MBI may be a warning sign for the early pathology of AD, and more attention should be paid on the number and duration of MBI symptoms. Conclusion: MBI may be an early sign and predictor of Alzheimer's disease dementia. Early intervention for MBI may have a positive effect on alleviating long-term cognitive decline.
Keywords: early predictor